The contractive function of the myocardium of the LV in the disturbance of homocysteine metabolism in IHD patients - Nikonenko, A. S.; Chmul, K. O.; Nikonenko, A. A.; Molodan, O. V.; Osaulenko, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Diseases of the cardiovascular system (ZSSS) – one of the most acute medical and social problems of modern society. It has now been established that in the progression of IHD and its complications, an increase in the level of homocysteine is essential. However, medical publications do not adequately illustrate the study of the effect of HHC on the course of atherosclerosis and the functional state of the myocardium, which requires a more detailed study of this problem. Purpose of the study: To study the functional state of the myocardium depending on the degree of hyperhomocysteinemia in patients with IHD requiring surgical measurement. Materials and methods. The study analyzed the laboratory data of 30 patients suffering from atherosclerosis. Depending on the degree of GGZ, the patients were divided into 3 groups. These changes in myocardial contractility were more pronounced in patients with HHC and multifocal atherosclerosis, which requires a more thorough medical correction after surgery. Results.Of practical interest is the analysis of patients and their deformation properties of the myocardium by the method of speckle tracking Echo-CG and Echo-KG, depending on the concentrations of GC of blood plasma, the number of coronary arteries and the prevalence of atherosclerosis. In our work comparing Echo-CS data, we found out that in patients of groups 1 and 2 and a group of healthy individuals, there was no significant difference in hemodynamic parameters, despite the difference in the GC level and prevalence of atherosclerosis. There are differences in patients in group 3, consisting of a reduced LVEF compared with the 1 st and 2 nd group. Using the method of speckle tracking Echo-CG, patients of the 1st group, that of the 2nd group, and especially of the 3rd group with multifocal atherosclerosis and significantly higher homocysteine parameters, had changes in the functional state of the myocardium-a decrease in global longitudinal and circular deformation, compared with the usual Echo-Ks methods. Consequently, the greater the prevalence of atherosclerosis and the level of HC, the more pronounced changes in deformation properties of the myocardium of the LV. Dependence of the degree of decrease in longitudinal, circular LV deformation in basal sections and twisting on the number of affected CA was noted. Conclusions. Hyperhomocysteinemia is a risk factor for the development of coronary heart disease and is associated with an unfavorable course of coronary disease. We found that the higher the level of homocysteine, the more pronounced course of atherosclerosis and more pronounced changes in the functional state of the myocardium.